El Fototropismo en Plantas - Raya Pérez, Juan Carlos (Acta Universitaria, 2003)
Studies on the molecular basis of phototropism have led to the isolation of the phototropin gene. Others genes involved in the phototropic response such as nph4, nph3 and rpt2 have also been isolated. It isexpected that in the near future it will be established what is the participation of the phototropins, unknown until know, by means of signalling.
Keywords: Array; Array; Array; Array; Array